A Novel in vitro Human Macrophage Model to Study the Persistence of Mycobacterium tuberculosis Using Vitamin D3 and Retinoic Acid Activated THP-1 Macrophages - Estrella, Jaymie; Kan-Sutton, Celestine; Gong, King; Eissa, Tony N.; Rajagopalan, Malini; Lewis, Dorothy; Hunter, Robert; Jagannath, Chinnaswamy (Frontiers in Microbiology, 2011)
Mycobacterium tuberculosis (Mtb) replicates within the human macrophages and we investigated the activating effects of retinoic acid (RA) and vitamin D3 (VD) on macrophages in relation to the viability of Mtb. A combination of these vitamins (RAVD) enhanced the receptors on THP-1 macrophage (Mannose receptor and DC-SIGN) that increased mycobacterial uptake but inhibited the subsequent intracellular growth of Mtb by inducing reactive oxygen species (ROS) and autophagy. RAVD also enhanced antigen presenting and homing receptors in THPs that suggested an activated phenotype for THPs following RAVD treatment. RAVD mediated activation was also associated with a marked phenotypic change in Mtb infected THPs that fused with adjacent cells to form multinucleate giant cells (MNGCs). Typically MNGCs occurred over 30 days of in vitro culture and contained non-replicating persisting Mtb for as long as 60 days in culture. Latent tuberculosis occurs in over a third of the mankind and we propose that RAVD mediated induction of persistence of Mtb within human macrophages provides a novel model to develop therapeutic means.